The detection of new highly productive isolates of fungus Pleurotus ostreatus (Jacq.: Fr.) Kummer by their tolerance to coefficient of habitus - Дорошкевич, Н. В.; Шевкопляс, В. М. (Scientific Progress & Innovations, 2012)
In this work the estimation of economical and biological quantities of new isolates of the P. ostreatus fungus in intensive cultivation condition on solid substrate (husks sunflower) as most wide spreading in Ukraine was made. It was found out that all cultures of oyster mushroom are able to form fruiting bodies without temperature shock and additional influence of other external factors. The morphological and biological peculiarity of new isolates of the P. ostreatus fungus that is a size of fruiting bodies, fruiting bodies and accretes quantity and size of hatfungus has been found. The calculation of fruiting bodies habitus of the new isolates of oyster mushroom has been done. By resulted experiments the most perspective isolates (B-99 and K-99) against with HK-35 control strain for industrial cultivation has been found.